Monitoring of atmospheric corrosion and dewing process by interlacing copper electrode sensor. (15th April 2019) - Wan, Shan; Hou, Jian; Zhang, Ze-Fan; Zhang, Xin-xin; Dong, Ze-Hua
Highlights: Formation of TEL is in situ monitored by EIS, ATR-FTIR and video observation. Thickening and thinning of TEL could be monitored by comb-like copper sensor. Dewing could be monitored sensitively in the high-low temperature cyclic tests. Abstract: A novel dewing sensor consisting of two interlacing (comb-like) copper electrodes was fabricated by photolithography to monitor the formation and evaporation process of thin electrolyte layer (TEL), as well as atmospheric corrosion of copper during wetting-drying and high-low temperature cyclic tests. Thanks to the ultra-narrow space between the comb-like electrodes, the sensor can probe earlier dew condensation on Cu even at low relative humidity. Moreover, the thickness of TEL can be easily calculated based on high-frequency impedance during the drying process of TEL.